The Holstein–Lewis humerus shaft fracture in children: are they different from adults?. Issue 3 (20th May 2021) - Singh, Vivek; Hayes, Hannah V.; Kazemi, Namdar; Dey, Sukalyan; Parikh, Shital N.
Abstract : Spiral fractures in the distal third humerus shaft (Holstein–Lewis fracture pattern) have been associated with high risk of radial nerve palsy in adults and surgical treatment is recommended as the treatment of choice to remove the entrapped nerve from the fracture site. But this association and treatment approach has not been evaluated in pediatric humerus shaft fractures. In a retrospective study, 38 pediatric patients with Holstein–Lewis fracture configuration were identified after a review of radiographs of 1609 patients with humerus shaft fracture. Age at initial presentation, sex, mechanism of injury, side involved, presence of any associated injuries, neurovascular status, radial nerve status, fracture management, and any complications were noted. Thiry-three (86.8%) patients with mean age 10.1 ± 3.7 years were successfully treated by closed methods. Five patients (13.2%) with mean age 15.2 ± 2.6 years underwent surgical treatment. Contrary to adults, no children/adolescents had radial nerve palsy at presentation. Radiographic healing was acceptable in all cases at latest follow-up. Holstein–Lewis fracture behaves differently in children with no increased risk of radial nerve palsy. Majority can be treated conservatively. The thick periosteum in children may offer protection to the radial nerve and may be responsible for the success of closed treatment.